THE ROLE OF SYNONYMS IN INCREASING THE VOCABULARY OF STUDENTS (American Journal of Pedagogical and Educational Research, 2025)
This article analyzes the scientific and theoretical substantiation of the role of synonyms in increasing the vocabulary of students and the development of the structural components of speech competence, the development of oral and written speech, the independent expression of opinion, the development of a creative approach to text creation and the mastery of speech culture.